PERANAN PENYULUH PERTANIAN LAPANGAN DALAM PENERAPAN PROGRAM AKSI DESA MANDIRI PANGAN KHUSUSNYA USAHATANI JAGUNG DI KECAMATAN JALUKO KABUPATEN MUARO JAMBI - Mahendi, Tedi; Denmar, Denny; Mara, Armen (Universitas Jambi, 2013)
This study aims at 1 ) . To determine the application of the five technologies maize farming town in the district of Outer Muaro Jambi Jambi . 2 ) . To determine the role of PPL in corn farming technology adoption in the Outer City District Muaro Jambi Jambi . This study was conducted on 04 July to 4 August 2013 . Location of the research done purposively . The research was conducted in the district of Jambi Outside the City by taking two villages namely Sungai Durian and Village Muaro Pijoan . The sample used in this study were 44 poor families who follow the program of action independent village food especially maize farming , this sampling method sampling saturated or another term census . The research data collection consists of primary and secondary data , to obtain more in-depth data conducted interviews and observation . The results showed that perenan Agricultural Penuluh through the role of educators , pendaming role and the role of supervisors is high , but of the role of Agricultural Extension Workers is the most dominant Perana penddik . There is a real connection between the role of agricultural extension field with the implementation of the action program independent village food especially maize farming , the role demanded of corn farming in the affected PPL particularly good farming practices , so that farmers will get the maximum results . Keyword : The Role of Agricultural Extension, Application of Corn Farming